Une guerre en marge - Victor Barbat (Conserveries Mémorielles)
In September 1938, filmmaker Roman Karmen went to China to cover the second Sino-Japanese War. For a year, the Soviet Documentarist crossed the country on behalf of The Moscow Newsreel Studio. The propaganda campaign that followed on screens is a total failure. The news serial China Fights stopped and the conflict cover is largely marginalized from 1939. Why? What were the implications of Moscow's international stance on the distribution of films? While presenting the main goals of this propaganda campaign, and to understand the reasons for its failure we put into perspective the content of the distributed films and the choices made by Karmen with the Kremlin ambiguous policy between July 1938 and August 1939.